Strategi Komunikasi Pemasaran Kopi TM 100 dalam Meningkatkan Penjualan di Kabupaten Batu Bara - Zannah, Nurul; Syahminan, Muhammad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to analyze the marketing communication strategies implemented by Kopi TM 100 in increasing sales in Batu Bara Regency. The approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants consist of one café supervisor and 14 active consumers, selected purposively. The results of the study indicate that Kopi TM 100's marketing communication strategies are still conventional, relying on word-of-mouth promotion, banners, seasonal events, and direct service. Despite its simplicity, this strategy is effective due to the café’s comfortable atmosphere, affordable prices, and positive customer experiences. However, limitations in digital promotion are the main obstacle, such as minimal social media activity, the absence of a customer loyalty program, and the lack of a dedicated marketing team. Findings also indicate that sales spikes only occur during specific periods, such as Ramadan and weekends when events are held. Therefore, there is a need to strengthen integrated digital strategies to ensure that marketing communication is not only effective locally but also sustainable and reaches a wider consumer base. This study recommends a community-based approach supported by digital marketing as the ideal strategy for local SMEs.